2019
DOI: 10.1016/j.foodchem.2018.12.107
|View full text |Cite
|
Sign up to set email alerts
|

Floral nectar chitinase is a potential marker for monofloral honey botanical origin authentication: A case study from loquat (Eriobotrya japonica Lindl.)

Abstract: Floral nectar chitinase is a potential marker for monofloral honey botanical origin authentication: a case study from loquat (Eriobotrya japonica Lindl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…In the Coomassie brilliant blue-stained gel, all honeys exhibited 4–5 apparent protein bands with molecular weights ranging from 43 to 97.4 kDa, although their molecular weights and contents differed (Figure A). This demonstrated that the proteins in the six Chinese honeys dominantly concentrated within this molecular weight interval, in line with the results of Di Girolamo et al and Song et al, who investigated the extracted proteins of other monofloral honeys from chestnut, sunflower, orange, and loquat. The proteins identified in honey thus far are mainly derived from bees, such as the family of major royal jelly proteins (MRJPs), α-glucosidase, amylase, glucose oxidase, glucose dehydrogenase, etc., whose molecular weights were exactly within the range of 50–80 kDa. , In addition, the jujube, longan and A. cerana honey contained more abundant proteins with higher molecular weights >97.4 kDa (Figure A).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In the Coomassie brilliant blue-stained gel, all honeys exhibited 4–5 apparent protein bands with molecular weights ranging from 43 to 97.4 kDa, although their molecular weights and contents differed (Figure A). This demonstrated that the proteins in the six Chinese honeys dominantly concentrated within this molecular weight interval, in line with the results of Di Girolamo et al and Song et al, who investigated the extracted proteins of other monofloral honeys from chestnut, sunflower, orange, and loquat. The proteins identified in honey thus far are mainly derived from bees, such as the family of major royal jelly proteins (MRJPs), α-glucosidase, amylase, glucose oxidase, glucose dehydrogenase, etc., whose molecular weights were exactly within the range of 50–80 kDa. , In addition, the jujube, longan and A. cerana honey contained more abundant proteins with higher molecular weights >97.4 kDa (Figure A).…”
Section: Resultssupporting
confidence: 89%
“…Di Girolamo et al 17 investigated the possibility of proteo-typing honey varieties using gel-based proteomic approach, and identified one plant original protein (glyceraldehyde-3-phosphate dehydrogenase), but it provided limited utility for determining botanical origin. A recent study by Song et al 18 demonstrated that Chitinase was a potential marker to distinguish loquat honey from rapeseed honey by examination of the nectar-origin enzyme activity in honey. Nonetheless, to our knowledge, there has not been an identified protein marker to distinguish the botanical origin of honey.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, chitinase is a potential marker for authenticating the botanical origin of loquat honey. 72 Proteomics has also been applied to identify honey of different origins providing outstanding capability for identifying unique proteins in honey. These methods rely on protein sequence information in a database coupled with the analytical power of mass spectrometry.…”
Section: Acs Foodmentioning
confidence: 99%
“…There are many works dealing with the problem of honey adulteration [ 7 , 14 , 15 , 16 , 17 ] and less works, where the knowledge of rheology is used for this purpose [ 11 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%